2021
DOI: 10.3390/antibiotics10111329
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Isolated from the Oral Cavity: Phage Susceptibility in Relation to Antibiotic Resistance

Abstract: Nowadays, research on bacteriophage therapy and its potential use in combination with antibiotics has been gaining momentum. One hundred and ten oral Staphylococcus aureus isolates were phage-typed and their antibiotic resistance was determined by standard and molecular methods. The prevalence of MSSA and MRSA strains was 89.1% and 10.9%, respectively. Nearly all (91.8%) analyzed isolates, whether MSSA or MRSA, were susceptible to the phages used from the international set. The highest lytic activity showed ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…The most frequent bacteria found in this study were Staphylococcus aureus 35(17.5%). But in contrast with other studies, this bacteria appear as the second most frequently found Grampositive cocci after Streptococci, especially species from the viridans group in Ogun State, Nigeria [21] and other Countries [25,34,35,36,37] but in line with the studies from two studies in Nigeria were 53.4%,14.2% [20,38] and a study in Poland 91.8% [30] Staphylococcus aureus predominant the Oral cavity. Earlier findings have also revealed that S. aureus was found at higher levels in the oral cavity and with greater prevalence, in periodontitis than in nonperiodontitis subjects [19,39] while Fritschi et al [40] found higher levels of S. aureus in aggressive than chronic periodontitis subjects.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The most frequent bacteria found in this study were Staphylococcus aureus 35(17.5%). But in contrast with other studies, this bacteria appear as the second most frequently found Grampositive cocci after Streptococci, especially species from the viridans group in Ogun State, Nigeria [21] and other Countries [25,34,35,36,37] but in line with the studies from two studies in Nigeria were 53.4%,14.2% [20,38] and a study in Poland 91.8% [30] Staphylococcus aureus predominant the Oral cavity. Earlier findings have also revealed that S. aureus was found at higher levels in the oral cavity and with greater prevalence, in periodontitis than in nonperiodontitis subjects [19,39] while Fritschi et al [40] found higher levels of S. aureus in aggressive than chronic periodontitis subjects.…”
Section: Discussioncontrasting
confidence: 51%
“…Nevertheless, there is a controversy about whether non-oral bacteria are merely transient or unique to this niche but in recent times substantial evidence in different studies has highlighted the role of these bacteria in dental disease either with coordinated co-operative behaviors in the presence of normal oral microbiota [1,6,25,30,31,32]. Additionally, some of these non-oral bacteria isolates from the oral cavity of patients with dental disease in this study, have been reported to be genetically different from strains from other parts of the human body [33], which could potentially lead to another understanding of the ecosystem of the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…In the dental field, it has been estimated that the carrier prevalence of S. aureus in healthy adults varies from 24% to 84% Donkor and Kotey (2020) . Additionally, the oral cavity is a source for cross infection and dissemination of the infection directly into the bloodstream, increasing the likelihood of septicemia and possibly death McCormack et al (2015) ; Garbacz et al (2021) ; Jevon et al (2021) .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 68.2% of our isolates were resistant to ciprofloxacin, an antibiotic that was not available in the 1950s, indicating recent acquisition of ciprofloxacin resistance by these isolates. In contrast, a recent study conducted in Poland revealed that all S. aureus phage 80/81 strains obtained from patients with oral infection were sensitive to ciprofloxacin [ 25 ]. Resistance to tetracycline and ciprofloxacin has also been reported in ST30-MRSA isolates [ 15 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a recent study conducted in Poland revealed that all S. aureus phage 80/81 strains obtained from patients with oral infection were sensitive to ciprofloxacin [ 25 ]. Resistance to tetracycline and ciprofloxacin has also been reported in ST30-MRSA isolates [ 15 , 24 , 25 ]. Although the isolates in this study were susceptible to erythromycin and clindamycin, 71% and 63% of CC30-MSSA causing ocular infections in patients in the USA were resistant to erythromycin and clindamycin, respectively [ 21 ].…”
Section: Discussionmentioning
confidence: 99%